Effect of postbiotics on the productive traits and economic efficiency of broiler chickens - Al-Salhi, Ahmed A.; Al-Shatty, Sabah M.; Al-Imara, Eman A.; Al-Saeedi, Nawar K. (Indonesian Journal of Microbiology, 2024)
The metabolized substance was produced in the laboratory (postbiotics), according to three successive stages. The first stage included: isolating and identifying lactic acid bacteria from the ileum area in the small intestine of poultry, while the second stage included: activating the isolated bacteria on sterilized sorted milk media for three consecutive times. The third stage included: producing the biologically metabolized substance or biologically active compounds, in the form of a fine powder. This substance was added to the diets of broilers at a level of (0, 1, and 2) g /kg feed, for three experimental treatments, T0, T1, and T2, respectively, during the rearing period of 35 days. To study its effect on the productive traits and economic efficiency of broilers. The results of the statistical analysis showed: a significant improvement (P≤0.05) in the rates of body weight and weight gain, in addition to a significant improvement (P≤0.05) in the food conversion rate and in the economic efficiency measure in favor of the postbiotics T1 and T2 treatments compared to the control treatment. T0, while there are no significant differences in the rate of feed consumption between all the treatments studied.